Encryption and display of multiple-image information using computer-generated holography with modified GS iterative algorithm - Xiao, Dan; Li, Xiaowei; Liu, Su-Juan; Wang, Qiong-Hua (Optics communications, 2018)
In this paper, a new scheme of multiple-image encryption and display based on computer-generated holography (CGH) and maximum length cellular automata (MLCA) is presented. With the scheme, the computer-generated hologram, which has the information of the three primitive images, is generated by modified Gerchberg–Saxton (GS) iterative algorithm using three different fractional orders in fractional Fourier domain firstly. Then the hologram is encrypted using MLCA mask. The ciphertext can be decrypted combined with the fractional orders and the rules of MLCA. Numerical simulations and experimental display results have been carried out to verify the validity and feasibility of the proposed scheme.